Trophoblast cell surface antigen 2 expression predicts outcome in oral squamous cell carcinomas. (5th March 2021) - Dourado, Mauricio Rocha; Machado, Renato Assis; Paranaíba, Lívia Máris Ribeiro; González‐Arriagada, Wilfredo Alejandro; da Silva, Sabrina Daniela; Sawazaki‐Calone, Íris; Graner, Edgard; Salo, Tuula; Coletta, Ricardo D.
Abstract: Background: Trophoblast cell surface antigen 2 (TROP2) has unclear clinical role in oral squamous cell carcinomas (OSCC). Here, we investigated the association of TROP2 immunoexpression with clinicopathological parameters and survival of OSCC patients. Subjects and Methods: Cancer‐specific survival (CSS) and disease‐free survival (DFS) were assessed in a cohort composed of 266 OSCC. An independent cohort with 88 OSCC samples matched with the normal oral tissue, as well as 17 metastatic lymph nodes, was used for validation. Results: Multivariate analysis showed TROP2 as an independent marker of favorable prognosis for both CSS (HR: 0.60, 95% CI: 0.40–0.90, p  = .01) and DFS (HR: 0.57, 95% CI: 0.36–0.89, p  = .01). Furthermore, TROP2 protein expression was significantly higher in morphologically normal tissues compared to primary tumors ( p  < .0001) and lymph node metastases ( p  = .001), and it was significantly associated with CSS (HR: 0.26, 95% CI: 0.09–0.74, p  = .008) in the validation cohort. A pooled mRNA analysis performed on the Oncomine™ database confirmed the underexpression in OSCC compared with normal tissues ( p  = .014). Conclusions: In summary, our results point to a favorable prognostic significance of TROP2 overexpression in a large cohort of oral cancer patients, suggesting it as an attractive clinical marker.